A comprehensive retrospect on the current perspectives and future prospects of pneumoconiosis - Hou, Xiaomin; Wei, Zhengqian; Jiang, Xuelu; Wei, Chengjie; Dong, Lin; Li, Yanhua; Liang, Ruifeng; Nie, Jisheng; Shi, Yiwei; Qin, Xiaojiang (Frontiers in Public Health, 2025)
Pneumoconiosis is a widespread occupational pulmonary disease caused by inhalation and retention of dust particles in the lungs, is characterized by chronic pulmonary inflammation and progressive fibrosis, potentially leading to respiratory and/or heart failure. Workers exposed to dust, such as coal miners, foundry workers, and construction workers, are at risk of pneumoconiosis. This review synthesizes the international and national classifications, epidemiological characteristics, strategies for prevention, clinical manifestations, diagnosis, pathogenesis, and treatment of pneumoconiosis. Current research on the pathogenesis of pneumoconiosis focuses on the influence of autophagy, apoptosis, and pyroptosis on the progression of the disease. In addition, factors such as lipopolysaccharide and nicotine have been found to play crucial roles in the development of pneumoconiosis. This review provides a comprehensive summary of the most fundamental achievements in the treatment of pneumoconiosis with the purpose of indicating the future direction of its treatment and control. New technologies of integrative omics, artificial intelligence, systemic administration of mesenchymal stromal cells have proved useful in solving the conundrum of pneumoconiosis. These directional studies will provide novel therapeutic targets for the treatment of pneumoconiosis.